PE / PA symmetric film and preparation method thereof
By adopting a seven-layer symmetric structure and a PE/PA symmetric film with modified high-density polyethylene, the mechanical properties of the traditional film are solved, and the stiffness and strength are achieved. It is suitable for the high-end packaging material market and maintains good processing performance.
Patent Information
- Application Number
- CN202411916442.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Traditional PE/PA symmetrical films have shortcomings in terms of mechanical properties, especially their low stiffness and tensile strength, which limits their application in the high-end packaging material market.
Using a seven-layer PE/PA symmetrical film with a symmetric structure, modified high-density polyethylene and linear low-density polyethylene were used to replace low-density polyethylene, and the high-density polyethylene was modified by an oxyalkylated organic solvent lignin-g-PLA graft copolymer to improve its toughness and compatibility.
It significantly improves the stiffness and strength of PE/PA symmetric films, meets the needs of high-performance packaging materials, and extends the service life of the film while maintaining good processing performance.
Abstract
Description
Technical Field
[0001] The present application relates to the field of packaging film material technology, and in particular to a PE / PA symmetric film and a preparation method thereof. Background Art
[0002] In the field of polymer composite science and technology, PE (polyethylene) / PA (polyamide) symmetric membranes have shown wide application potential in food packaging, medical packaging, agricultural covering films and other fields due to their excellent physical properties, such as good barrier properties, chemical resistance and certain flexibility. However, when traditional low-density polyethylene (LDPE) is used as the main matrix material of PE / PA membranes, despite its significant processing convenience and cost-effectiveness, the prepared membranes have obvious shortcomings in mechanical properties, especially stiffness and tensile strength. This defect limits the application of PE / PA symmetric membranes in the high-end packaging material market that requires higher strength support, tear resistance or durability.
[0003] In order to improve the mechanical properties of PE / PA symmetric membranes, polymer blending technology is often used in the prior art, that is, LDPE is blended with other specific engineering plastics in order to improve the mechanical properties of the membrane through the interaction between different polymer chains. Although this method improves the strength and stiffness of the membrane to a certain extent, the compatibility problems between different polymers during the blending process often lead to the deterioration of the processing performance of the membrane material. Therefore, providing a method that can effectively improve the mechanical properties of PE / PA symmetric membranes without sacrificing their processing performance and long-term stability has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to improve the mechanical strength of the PE / PA symmetric membrane, the present application provides a PE / PA symmetric membrane and a preparation method thereof.
[0005] The present application provides a PE / PA symmetric membrane, which adopts the following technical solution: A PE / PA symmetric film, which comprises, from the outside to the inside, an outer layer, a second outer layer, a first adhesive layer, a middle layer, a second adhesive layer, an inner layer and a second inner layer; the raw materials of the outer layer and the second inner layer are modified high-density polyethylene, the raw materials of the outer second layer and the inner layer are linear low-density polyethylene, the raw materials of the first adhesive layer and the second adhesive layer are TIE resin, and the raw material of the middle layer is PA resin.
[0006] By adopting the above-mentioned technical scheme, the PE / PA symmetric film of the present application adopts a seven-layer symmetrical structure, and the raw materials use high-density polyethylene and linear low-density polyethylene instead of low-density polyethylene, which significantly improves the stiffness and strength of the PE / PA symmetric film to meet the needs of high-performance packaging materials. By modifying the high-density polyethylene, the toughness of the high-density polyethylene is significantly improved, thereby further improving the mechanical properties and service life of the PE / PA symmetric film.
[0007] Preferably, the mass ratio of the raw materials of the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer is 0.156-0.168: 0.195-0.203: 0.077-0.087: 0.113-0.0125: 0.077-0.087: 0.195-0.203: 0.156-0.168.
[0008] Preferably, the mass ratio of the raw materials of the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer is 0.162:0.199:0.082:0.119:0.082:0.199:0.162.
[0009] Preferably, the modified high-density polyethylene is prepared from the following raw materials in parts by weight: 50-60 parts of high-density polyethylene and 10-12 parts of oxyalkylated organic solvent lignin-g-PLA graft copolymer.
[0010] By adopting the above technical scheme, high-density polyethylene is modified by using an oxyalkylated organic solvent lignin-g-PLA graft copolymer. Lignin contains a large number of active functional groups such as phenolic hydroxyl groups and aliphatic hydroxyl groups, and is an ideal material for preparing green polymer materials. The oxyalkylated organic solvent lignin-g-PLA graft copolymer is prepared from the following raw materials in parts by weight: 0.01-0.03 parts of oxyalkylated organic solvent lignin, 1-3 parts of L-lactide, 0.05-0.15 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, 10-20 parts of acetic acid, and 45-60 parts of methanol.
[0011] Preferably, the oxyalkylated organic solvent lignin is prepared from the following raw materials in parts by weight: 5-10 parts of organic solvent lignin, 0.6-1.2 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, 79-108 parts of propylene carbonate, and 200-300 parts of water.
[0012] By adopting the above technical scheme, the present application uses propylene carbonate (PC) to carry out oxyalkylation modification on organic solvent lignin (OL), thereby increasing the number of aliphatic hydroxyl groups in the organic solvent lignin, and then the oxyalkylated lignin is ring-opening polymerized with L-lactide to prepare a graft copolymer. The obtained oxyalkylated organic solvent lignin-g-PLA graft copolymer can not only effectively improve the strength and toughness of high-density polyethylene, but also the oxyalkylated organic solvent lignin-g-PLA graft copolymer has good compatibility with high-density polyethylene and has good processing performance.
[0013] Preferably, the method for preparing the oxyalkylated organic solvent lignin comprises the following steps: Add organic solvent lignin, propylene carbonate and 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150-190°C, and stir it magnetically for 3-5 hours. After the reaction is completed, drop the reaction solution into water and stir it for 1-3 hours. After vacuum filtration, obtain a solid product, wash it several times and then freeze-dry it to obtain oxyalkylated organic solvent lignin.
[0014] Preferably, the method for preparing the oxyalkylated organic solvent lignin-g-PLA graft copolymer comprises the following steps: Add oxyalkylated organic solvent lignin, L-lactide and 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill with nitrogen and seal, heat in an oil bath to 130-150° C. and stir magnetically for 3-4 hours, then add acetic acid to stop the reaction, add methanol, stir for 1-2 hours, and obtain a solid product by centrifugation. After washing several times, dry in a vacuum drying oven at 50-60° C. for 24-30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer.
[0015] Preferably, the method for preparing the modified high-density polyethylene comprises the following steps: The high-density polyethylene is dried under vacuum at 75-85° C. for 12-15 hours; the dried high-density polyethylene and the oxyalkylated organic solvent lignin-g-PLA graft copolymer are placed in a mixer, and melt-blended at 160-180° C. and a screw speed of 60-80 rpm for 10-20 minutes to obtain a modified high-density polyethylene.
[0016] The present application also provides a method for preparing a PE / PA symmetric membrane, which adopts the following technical solution: A method for preparing a PE / PA symmetric membrane comprises the following steps: S1. Weigh the raw materials of the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer according to the mass ratio, put the raw materials into the hopper of the seven-layer co-extrusion film blowing machine in turn, set the screw barrel temperature corresponding to the hopper to 195-210°C, and then extrude the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer base film by screw extrusion; S2. The outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the inner second base film are passed through the die head of the seven-layer co-extrusion film blowing machine under the action of the screw, and are extruded and blown to form a finished film. The die head temperature of the seven-layer co-extrusion film blowing machine is set to 195-210°C, and the blowing ratio is 1:1.3-1.5.
[0017] By adopting the above technical solution, a seven-layer co-extrusion blown film mechanism is used to produce the film, which has many advantages such as high process stability, high production efficiency, excellent film performance and convenient operation, and can effectively obtain a PE / PA symmetrical film with mechanical properties.
[0018] In summary, the present application includes at least one of the following beneficial technical effects: 1. By adopting the above technical solution, the PE / PA symmetric film of the present application adopts a seven-layer symmetric structure, and the raw materials use high-density polyethylene and linear low-density polyethylene instead of low-density polyethylene, which significantly improves the stiffness and strength of the PE / PA symmetric film to meet the needs of high-performance packaging materials, and by modifying the high-density polyethylene, the toughness of the high-density polyethylene is significantly improved, thereby further improving the mechanical properties and service life of the PE / PA symmetric film; 2. By adopting the above-mentioned technical scheme, the present application uses propylene carbonate (PC) to carry out oxyalkylation modification on the organic solvent lignin (OL), thereby increasing the number of aliphatic hydroxyl groups in the organic solvent lignin, and then the oxyalkylated lignin is ring-opening polymerized with L-lactide to prepare a graft copolymer. The obtained oxyalkylated organic solvent lignin-g-PLA graft copolymer can not only effectively improve the strength and toughness of high-density polyethylene, but also the oxyalkylated organic solvent lignin-g-PLA graft copolymer has good compatibility with high-density polyethylene and has good processing performance. DETAILED DESCRIPTION
[0019] The present application is further described in detail below with reference to the embodiments.
[0020] Preparation Example Preparation Example 1 T1. Add 5 g of organic solvent lignin, 79 g of propylene carbonate and 0.6 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150 ° C, and stir it magnetically for 3 hours; after the reaction is completed, drop the reaction solution into 200 g of water and stir it for 1 hour, and obtain a solid product by vacuum filtration, wash it with deionized water 3 times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.01 g of the oxyalkylated organic solvent lignin prepared by T1, 1 g of L-lactide and 0.05 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 130°C and stir it magnetically for 3 hours, then add 10 g of acetic acid to stop the reaction, then add 45 g of methanol, stir it for 1 hour, centrifuge it at 10000 rpm to obtain a solid product, wash it with deionized water 3 times, and dry it in a vacuum drying oven at 50°C for 30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 50g of high-density polyethylene under vacuum at 75°C for 12h; put the dried high-density polyethylene and 10g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 160°C and a screw speed of 60rpm for 10min to obtain modified high-density polyethylene.
[0021] Preparation Example 2 T1. Add 7.5 g of organic solvent lignin, 94 g of propylene carbonate and 0.9 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 170 ° C, and stir it magnetically for 4 hours; after the reaction is completed, drop the reaction solution into 250 g of water and stir it for 2 hours, and obtain a solid product by vacuum filtration, wash it with deionized water three times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.01 g of the oxyalkylated organic solvent lignin prepared by T1, 1 g of L-lactide and 0.05 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 130°C and stir it magnetically for 3 hours, then add 10 g of acetic acid to stop the reaction, then add 45 g of methanol, stir it for 1 hour, centrifuge it at 10000 rpm to obtain a solid product, wash it with deionized water 3 times, and dry it in a vacuum drying oven at 50°C for 30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 50g of high-density polyethylene under vacuum at 75°C for 12h; put the dried high-density polyethylene and 10g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 160°C and a screw speed of 60rpm for 10min to obtain modified high-density polyethylene.
[0022] Preparation Example 3 T1. Add 10g of organic solvent lignin, 108g of propylene carbonate and 1.2g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 190°C, and stir it magnetically for 5h; after the reaction is completed, drop the reaction solution into 300g of water and stir it for 3h, and obtain a solid product by vacuum filtration, wash it with deionized water 3 times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.01 g of the oxyalkylated organic solvent lignin prepared by T1, 1 g of L-lactide and 0.05 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 130°C and stir it magnetically for 3 hours, then add 10 g of acetic acid to stop the reaction, then add 45 g of methanol, stir it for 1 hour, centrifuge it at 10000 rpm to obtain a solid product, wash it with deionized water 3 times, and dry it in a vacuum drying oven at 50°C for 30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 50g of high-density polyethylene under vacuum at 75°C for 12h; put the dried high-density polyethylene and 10g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 160°C and a screw speed of 60rpm for 10min to obtain modified high-density polyethylene.
[0023] Preparation Example 4 T1. Add 5 g of organic solvent lignin, 79 g of propylene carbonate and 0.6 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150 ° C, and stir it magnetically for 3 hours; after the reaction is completed, drop the reaction solution into 200 g of water and stir it for 1 hour, and obtain a solid product by vacuum filtration, wash it with deionized water 3 times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.02 g of the oxyalkylated organic solvent lignin prepared by T1, 2 g of L-lactide and 0.1 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 140°C and stir it magnetically for 3.5 hours, then add 15 g of acetic acid to stop the reaction, then add 52 g of methanol, stir it for 1.5 hours, centrifuge it at 15000 rpm to obtain a solid product, wash it with deionized water three times, and dry it in a vacuum drying oven at 55°C for 27 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 50g of high-density polyethylene under vacuum at 75°C for 12h; put the dried high-density polyethylene and 10g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 160°C and a screw speed of 60rpm for 10min to obtain modified high-density polyethylene.
[0024] Preparation Example 5 T1. Add 5 g of organic solvent lignin, 79 g of propylene carbonate and 0.6 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150 ° C, and stir it magnetically for 3 hours; after the reaction is completed, drop the reaction solution into 200 g of water and stir it for 1 hour, and obtain a solid product by vacuum filtration, wash it with deionized water 3 times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.03 g of the oxyalkylated organic solvent lignin prepared by T1, 3 g of L-lactide and 0.15 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150°C and stir it magnetically for 4 hours, then add 20 g of acetic acid to stop the reaction, then add 60 g of methanol, stir it for 2 hours, centrifuge it at 20000 rpm to obtain a solid product, wash it with deionized water three times, and dry it in a vacuum drying oven at 60°C for 24 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 50g of high-density polyethylene under vacuum at 75°C for 12h; put the dried high-density polyethylene and 10g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 160°C and a screw speed of 60rpm for 10min to obtain modified high-density polyethylene.
[0025] Preparation Example 6 T1. Add 5 g of organic solvent lignin, 79 g of propylene carbonate and 0.6 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150 ° C, and stir it magnetically for 3 hours; after the reaction is completed, drop the reaction solution into 200 g of water and stir it for 1 hour, and obtain a solid product by vacuum filtration, wash it with deionized water 3 times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.01 g of the oxyalkylated organic solvent lignin prepared by T1, 1 g of L-lactide and 0.05 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 130°C and stir it magnetically for 3 hours, then add 10 g of acetic acid to stop the reaction, then add 45 g of methanol, stir it for 1 hour, centrifuge it at 10000 rpm to obtain a solid product, wash it with deionized water 3 times, and dry it in a vacuum drying oven at 50°C for 30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 55g of high-density polyethylene under vacuum at 80°C for 13.5h; put the dried high-density polyethylene and 11g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 170°C and a screw speed of 70rpm for 15min to obtain modified high-density polyethylene.
[0026] Preparation Example 7 T1. Add 5 g of organic solvent lignin, 79 g of propylene carbonate and 0.6 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150 ° C, and stir it magnetically for 3 hours; after the reaction is completed, drop the reaction solution into 200 g of water and stir it for 1 hour, and obtain a solid product by vacuum filtration, wash it with deionized water 3 times and freeze-dry it to obtain oxyalkylated organic solvent lignin; T2. Add 0.01 g of the oxyalkylated organic solvent lignin prepared by T1, 1 g of L-lactide and 0.05 g of 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 130°C and stir it magnetically for 3 hours, then add 10 g of acetic acid to stop the reaction, then add 45 g of methanol, stir it for 1 hour, centrifuge it at 10000 rpm to obtain a solid product, wash it with deionized water 3 times, and dry it in a vacuum drying oven at 50°C for 30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer; T3. Dry 60g of high-density polyethylene under vacuum at 85°C for 15h; put the dried high-density polyethylene and 12g of the oxyalkylated organic solvent lignin-g-PLA graft copolymer prepared by T2 into a mixer, and melt-blend them at 180°C and a screw speed of 80rpm for 20min to obtain modified high-density polyethylene. Example
[0027] Example 1 S1. A PE / PA symmetric film, comprising, from outside to inside, an outer layer, an outer second layer, a first adhesive layer, a middle layer, a second adhesive layer, an inner layer and an inner second layer; weigh 0.156g of modified high-density polyethylene as a raw material for the outer layer, 0.195g of linear low-density polyethylene as a raw material for the outer second layer, 0.077g of TIE resin as a raw material for the first adhesive layer, 0.113g of PA resin as a raw material for the middle layer, 0.077g of TIE resin as a raw material for the second adhesive layer, 0.195g of linear low-density polyethylene as a raw material for the inner layer and 0.156g of modified high-density polyethylene as a raw material for the inner second layer, the TIE resin used in this embodiment is an anhydride-modified ethylene-vinyl acetate copolymer, and the modified high-density polyethylene used is from Preparation Example 1; put the raw materials into the hopper of a seven-layer co-extrusion film blowing machine in turn, set the screw barrel temperature corresponding to the hopper to 195°C, and then extrude the outer layer, the outer second layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the inner second layer base film by screw extrusion; S2. The outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer base film are passed through the die head of a seven-layer co-extrusion film blowing machine under the action of a screw, and are extruded and blown to form a finished film. The die head temperature of the seven-layer co-extrusion film blowing machine is set to 195°C, and the blowing ratio is 1:1.3.
[0028] Example 2 S1. A PE / PA symmetric film, comprising, from outside to inside, an outer layer, an outer second layer, a first adhesive layer, a middle layer, a second adhesive layer, an inner layer and an inner second layer; weigh 0.162g of modified high-density polyethylene as a raw material for the outer layer, 0.199g of linear low-density polyethylene as a raw material for the outer second layer, 0.082g of TIE resin as a raw material for the first adhesive layer, 0.118g of PA resin as a raw material for the middle layer, 0.082g of TIE resin as a raw material for the second adhesive layer, 0.199g of linear low-density polyethylene as a raw material for the inner layer and 0.162g of modified high-density polyethylene as a raw material for the inner second layer, the TIE resin used in this embodiment is an ethylene-vinyl acetate copolymer modified by anhydride, and the modified high-density polyethylene used is from Preparation Example 1; put the raw materials into the hopper of a seven-layer co-extrusion film blowing machine in turn, set the screw barrel temperature corresponding to the hopper to 200°C, and then extrude the outer layer, the outer second layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the inner second layer base film by screw extrusion; S2. The outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer base film are passed through the die head of a seven-layer co-extrusion film blowing machine under the action of a screw, and are extruded and blown to form a finished film. The die head temperature of the seven-layer co-extrusion film blowing machine is set to 200°C, and the blowing ratio is 1:1.4.
[0029] Example 3 S1. A PE / PA symmetric film, comprising, from outside to inside, an outer layer, an outer second layer, a first adhesive layer, a middle layer, a second adhesive layer, an inner layer and an inner second layer; weigh 0.168g of modified high-density polyethylene as a raw material for the outer layer, 0.203g of linear low-density polyethylene as a raw material for the outer second layer, 0.087g of TIE resin as a raw material for the first adhesive layer, 0.125g of PA resin as a raw material for the middle layer, 0.087g of TIE resin as a raw material for the second adhesive layer, 0.203g of linear low-density polyethylene as a raw material for the inner layer and 0.168g of modified high-density polyethylene as a raw material for the inner second layer, the TIE resin used in this embodiment is an ethylene-vinyl acetate copolymer modified by anhydride, and the modified high-density polyethylene used is from Preparation Example 1; put the raw materials into the hopper of a seven-layer co-extrusion film blowing machine in turn, set the screw barrel temperature corresponding to the hopper to 210°C, and then extrude the outer layer, the outer second layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the inner second layer base film by screw extrusion; S2. The outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer base film are passed through the die head of a seven-layer co-extrusion film blowing machine under the action of a screw, and are extruded and blown to form a finished film. The die head temperature of the seven-layer co-extrusion film blowing machine is set to 210°C, and the blowing ratio is 1:1.5.
[0030] Example 4 The difference between Example 4 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Example 4 are from Preparation Example 2.
[0031] Example 5 The difference between Example 5 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Example 5 are from Preparation Example 3.
[0032] Example 6 The difference between Example 6 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Example 6 are from Preparation Example 4.
[0033] Example 7 The difference between Example 7 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Example 7 are from Preparation Example 5.
[0034] Example 8 The difference between Example 8 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Example 8 are from Preparation Example 6.
[0035] Example 9 The difference between Example 9 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Example 9 are from Preparation Example 7.
[0036] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the outer layer raw material is 0.150g of modified high-density polyethylene, the outer second layer raw material is 0.191g of linear low-density polyethylene, the first adhesive layer raw material is 0.072g of TIE resin, the middle layer raw material is 0.107g of PA resin, the second adhesive layer raw material is 0.072g of TIE resin, the inner layer raw material is 0.191g of linear low-density polyethylene, and the inner second layer raw material is 0.150g of modified high-density polyethylene.
[0037] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the outer layer raw material is 0.174g of modified high-density polyethylene, the outer second layer raw material is 0.207g of linear low-density polyethylene, the first adhesive layer raw material is 0.092g of TIE resin, the middle layer raw material is 0.131g of PA resin, the second adhesive layer raw material is 0.092g of TIE resin, the inner layer raw material is 0.207g of linear low-density polyethylene, and the inner second layer raw material is 0.174g of modified high-density polyethylene.
[0038] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the raw materials used for the outer layer and the inner second layer in Comparative Example 3 are unmodified high-density polyethylene.
[0039] Performance testing 1. The tensile strength and elongation at break of the PE / PA symmetric films obtained in Examples 1-9 and Comparative Examples 1-3 were tested using GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3 Film / sheet test conditions”. The results are shown in Table 1.
[0040] 2. While ensuring the flatness of the PE / PA symmetric film, take a 15mm×160mm long strip of polyester film sample along the longitudinal direction, place it horizontally, and clamp it for 20mm. The horizontal position difference between the free end and the clamping end is used as the evaluation standard for the stiffness of the PE / PA symmetric film. The smaller the horizontal difference, the better the stiffness of the PE / PA symmetric film. The results are shown in Table 1.
[0041] The specific test results are as follows: Table 1 Performance test results Tensile strength / MPa Elongation at break / % Stiffness / mm Example 1 51 665 26 Example 2 67 695 12 Example 3 58 680 18 Example 4 54 670 24 Example 5 52 662 25 Example 6 53 667 25 Example 7 51 662 27 Example 8 60 672 20 Example 9 54 668 22 Comparative Example 1 28 580 75 Comparative Example 2 31 593 80 Comparative Example 3 35 376 90 It can be seen from the test results in Table 1 that the PE / PA symmetric film and the preparation method thereof provided in the present application have high tensile strength and elongation at break of the obtained film, indicating that the PE / PA symmetric film provided in the present application has strong mechanical strength; the horizontal position difference between the free end and the clamping end of the film is small, indicating that the PE / PA symmetric film provided in the present application has good stiffness.
[0042] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A PE / PA symmetric membrane, characterized in that: The PE / PA symmetric film includes an outer layer, an outer second layer, a first adhesive layer, a middle layer, a second adhesive layer, an inner layer and an inner second layer from the outside to the inside; the raw materials of the outer layer and the inner second layer are modified high-density polyethylene, the raw materials of the outer second layer and the inner layer are linear low-density polyethylene, the raw materials of the first adhesive layer and the second adhesive layer are TIE resin, and the raw material of the middle layer is PA resin.
2. A PE / PA symmetric membrane according to claim 1, characterized in that: The mass ratio of the raw materials of the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer is 0.156-0.168: 0.195-0.203: 0.077-0.087: 0.113-0.0125: 0.077-0.087: 0.195-0.203: 0.156-0.
168.
3. A PE / PA symmetric membrane according to claim 2, characterized in that: The mass ratio of the raw materials of the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer is 0.162:0.199:0.082:0.119:0.082:0.199:0.
162.
4. A PE / PA symmetric membrane according to claim 1, characterized in that: The modified high-density polyethylene is prepared from the following raw materials in parts by weight: 50-60 parts of high-density polyethylene and 10-12 parts of oxyalkylated organic solvent lignin-g-PLA graft copolymer.
5. A PE / PA symmetric membrane according to claim 4, characterized in that: The oxyalkylated organic solvent lignin-g-PLA graft copolymer is prepared from the following raw materials in parts by weight: 0.01-0.03 parts of oxyalkylated organic solvent lignin, 1-3 parts of L-lactide, 0.05-0.15 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, 10-20 parts of acetic acid, and 45-60 parts of methanol.
6. A PE / PA symmetric membrane according to claim 5, characterized in that: The oxyalkylated organic solvent lignin is prepared from the following raw materials in parts by weight: 5-10 parts of organic solvent lignin, 0.6-1.2 parts of 1,8-diazabicyclo[5.4.0]undec-7-ene, 79-108 parts of propylene carbonate, and 200-300 parts of water.
7. A PE / PA symmetric membrane according to claim 6, characterized in that: The method for preparing the oxyalkylated organic solvent lignin comprises the following steps: Add organic solvent lignin, propylene carbonate and 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill it with nitrogen and seal it, heat it in an oil bath to 150-190°C, and stir it magnetically for 3-5 hours. After the reaction is completed, drop the reaction solution into water and stir it for 1-3 hours. After vacuum filtration, obtain a solid product, wash it several times and then freeze-dry it to obtain oxyalkylated organic solvent lignin.
8. The PE / PA symmetric membrane according to claim 5, characterized in that: The preparation method of the oxyalkylated organic solvent lignin-g-PLA graft copolymer comprises the following steps: Add oxyalkylated organic solvent lignin, L-lactide and 1,8-diazabicyclo[5.4.0]undec-7-ene into a pressure tube, fill with nitrogen and seal, heat in an oil bath to 130-150° C. and stir magnetically for 3-4 hours, then add acetic acid to stop the reaction, add methanol, stir for 1-2 hours, and obtain a solid product by centrifugation. After washing several times, dry in a vacuum drying oven at 50-60° C. for 24-30 hours to obtain an oxyalkylated organic solvent lignin-g-PLA graft copolymer.
9. A PE / PA symmetric membrane according to claim 4, characterized in that: The preparation method of the modified high-density polyethylene comprises the following steps: The high-density polyethylene is dried under vacuum at 75-85° C. for 12-15 hours; the dried high-density polyethylene and the oxyalkylated organic solvent lignin-g-PLA graft copolymer are placed in a mixer, and melt-blended at 160-180° C. and a screw speed of 60-80 rpm for 10-20 minutes to obtain a modified high-density polyethylene.
10. A method for preparing a PE / PA symmetric membrane according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh the raw materials of the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer according to the mass ratio, put the raw materials into the hopper of the seven-layer co-extrusion film blowing machine in turn, set the screw barrel temperature corresponding to the hopper to 195-210°C, and then extrude the outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the second inner layer base film by screw extrusion; S2. The outer layer, the second outer layer, the first adhesive layer, the middle layer, the second adhesive layer, the inner layer and the inner second base film are passed through the die head of the seven-layer co-extrusion film blowing machine under the action of the screw, and are extruded and blown to form a finished film. The die head temperature of the seven-layer co-extrusion film blowing machine is set to 195-210°C, and the blowing ratio is 1:1.3-1.5.
Citation Information
Patent Citations
Binder for coating of plastic substrates without chemical or physical pretreatment
CA2982264A1
polycarbonate resin composition
CN102264836A
Ultralow thickness PE / PA composite film and preparation method thereof
CN109572118A
Low-temperature heat-sealing composite packaging film made of single polyethylene material and preparation method of low-temperature heat-sealing composite packaging film
CN118342829A
Alkoxylation of lignins
US20190144674A1